(untitled) (Educational Dimension, 2020)
The purpose of the study is to reproduce the historical reconstruction of the educational process in the author schools of Ukraine during the eighteenth – early twenty-first centuries to determine their role in the development of the national education system. The article considers the author secondary educational establishments that play a special part at the present stage of development of a new Ukrainian school, as their creators and pedagogical teams seek and indicate the ways of innovative educational development, define new goals, develop the content of education, substantiate and implement alternative educational technologies. The author school is presented as an experimental educational institution, which activity is based on a pedagogical concept developed by a single teacher or author team. It is noted that the author school as a unique educational system has gone a long way in its historical development. The first author school was named “school without walls” headed by H. Skovoroda, whose main goal was to teach people the science of happy life. The peculiarities of the educational process in the most famous author schools in Ukraine of the twentieth century have been analyzed. The experience of the author schools of the period of independent Ukraine was studied and summarized.